Sustainable Management Strategy for Shifting Livelihoods from Charcoal Producer Communities to Coffee Farmers in Jatiarjo Village, Prigen District, Pasuruan Regency - Mulyono Wibisono; Agung Murti Nugroho; Sri Palupi Prabandari (Postgraduate, University of Mataram, 2024)
Communities at the foot of Mount Arjuno not only have the potential for coffee cultivation but also cattle rearing. Indirectly, the forest fires that occurred were the cause of the reduction in supporting materials to meet their livestock needs. However, this change brings a number of problems that need to be addressed. The SWOT method is used to understand in depth the internal and external factors that influence job transitions. AHP method is used to measure and assess the relative weight of each factor identified through SWOT analysis. The research results show that the management of the socio-economic impact of changing the behavior of charcoal makers to coffee farmers in Jatiarjo Village shows that this village has great potential to utilize supporting natural resources and rich local knowledge in coffee cultivation. The threat of climate change and fluctuations in coffee market prices must be anticipated with appropriate adaptation strategies. The AHP results show that human resource (HR) capacity development has the highest weight in strategic priorities, followed by socio-economic impacts, policy, market access, and the environment.